A Direct and Sensitive Method for Determination of 5-Fluorouracil in Colorectal Cancer Cells: Evaluating the Effect of Stromal Cell on Drug Resistance of Cancer Cells. (25th February 2021) - Xu, Fengjing; Wang, Zhipeng; Song, Xinhua; Zhang, Mengwei; Cui, Lili; Liu, Yanping; Yan, Hongxia; Gao, Shouhong; Liu, Yan; Chen, Wansheng
Abstract : Fibroblasts in the stroma play a critical role in tumor evolution. In this study, we assessed the influence of colonic fibroblasts on colon cancer cells treated with 5-fluorouracil (5-FU), and mouse colon cancer cell lines MC38 and colonic fibroblasts NIH3T3 were used in this study. A sensitive and rapid UHPLC-MS/MS method for the quantitation of 5-FU from the cell and their medium has been successfully developed and validated. The cells were lysed with methanol, and the mixture was evaporated and then redissolved to extract intracellular 5-FU. The analysis was performed on UHPLC-MS/MS using an Atlantis T3-C18 column (3 μ m, 2. 1 ∗ 100 mm) and gradient elution with acetonitrile and 0.1% formic acid in water. Method validation included the following parameters: the matrix effect range 88.82%–93.64% and the recovery range 93.52%–94.56%. The intraday and interday precision and accuracy were <11% and within ±6%, and the stability, specificity, carry-over, dilution effect, and linearity all conformed to the criteria. The method was applied to detect the concentration of 5-FU inside cells and cell culture medium. The preliminary results present that NIH3T3 could enhance the drug resistance of MC38 to 5-FU with a decreased intracellular concentration of 5-FU in MC38, which showed a positive relationship with NIH3T3 number.